Subjectivity, argumentation and (im)politeness - Fuentes Rodríguez, Catalina (Círculo de Lingüística Aplicada a la Comunicación, 2012)
Subjectivity is used in argumentation and (im)politeness. It is very effective in the persuasion: a) as a mechanism of reinforcement or attenuation of the (im)politeness, b) as a fallacious argument (argumentum ad hominem, ad baculum, ad misericordiam), c) as a means of ensuring the affiliation with the partner. It is used, therefore, as a qualifier of the argument, or as a kind of arguments that use emotions to achieve a greater effect on the receiver. The speaker does it in order to be polite with his interlocutor, or to reject it in a blunt way. In the latter case the discourse is impolite and the argument, a fallacy. But, contrary to expectations, it is highly profitable in different textual formats. In this work we analyse two highly persuasive discursive types, politics or advertising, attending recurrently the emotion as a strategy in their search for efficient communication. The methodological framework in which we operate is a comprehensive pragmalinguistics where converge enunciation theory, theory of argumentation or verbal politeness.